Dominant co-exposed {101}/{111} facet of Er-doped rutile TiO2 film via hydrothermal doping - N.K.A. Hamed, N.K.A. Hamed; N. Nafarizal, N. Nafarizal; M.K. Ahmad, M.K. Ahmad; A.B. Faridah, A.B. Faridah; M. Shimomura, M. Shimomura (Elsevier, 2023)
The origin of the improved performance of erbium-doped TiO2 film via the hydrothermal doping process is discussed. Facet engineering of rutile TiO2 on the surface atomic structure is known but the electronic structure has been rarely studied to date. Particularly, the dominant facet of rutile TiO2 has changed upon doping resulting with co-exposed {101}/{111} facet as shown in TEM results. The surface energy levels of the conduction band (CB) and valence band (VB) on different crystal surfaces change, and these variations in energy levels will cause the electrons and holes to gravitate toward different crystal faces and inhibit the electron-hole recombination.